2020
DOI: 10.19045/bspab.2020.90056
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and heritability analysis in rapeseed (Brassica napus L.) genotypes

Abstract: This investigation was made to find out new discoveries from the correlation and heritability for ten yield and participating attributes in eight rapeseed genotypes at the experimental field of Oil Seeds Section, Agriculture Research Institute, Tandojam during 2017-18 in a randomized complete block design entailing three replications. The analysis of variance articulated highly significant and significant differences for all the growth and yield supporting attributes. In case of correlation study, plant height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
1
2
0
Order By: Relevance
“…Our results were also in agreement of Sootaher et al [14] who worked on wheat. These results were also observed by [15], [6]. These results were also articulated by [17], [18], and suggested that the genotypes having genetic variability for different characters must be chosen for future breeding.…”
Section: Discussionsupporting
confidence: 67%
“…Our results were also in agreement of Sootaher et al [14] who worked on wheat. These results were also observed by [15], [6]. These results were also articulated by [17], [18], and suggested that the genotypes having genetic variability for different characters must be chosen for future breeding.…”
Section: Discussionsupporting
confidence: 67%
“…High estimates signified that environmental effects on seed cotton yield were in small quantity than genetic variance. Yield is the most vital discontinuously varying attribute factors (Wang et al, 2012;Zeng et al, 2017;Zhang et al, 2017;Laghari et al, 2020). Such investigations for yield of cotton were also made in the experiment of Naveed et al (2004).…”
Section: Boll Weight (G)mentioning
confidence: 99%
“…For NDF, H 2 resulted in 0.92, followed by 0.72 for PL, meaning that these traits are less influenced by the environment than the others. Other studies have also reported high R² magnitudes (above 0.89) for NDF (12,15,16). Meanwhile, NGP and M1000G presented intermediate R² (0.68 and 0.57, respectively), as previously found (9,11).…”
Section: Resultsmentioning
confidence: 82%